Clinical Outcomes of Patients With Osteosarcoma Experiencing Relapse or Progression: A Single-institute Experience. Issue 3 (10th April 2023) - Umeda, Katsutsugu; Sakamoto, Akio; Noguchi, Takashi; Uchihara, Yoshinori; Kobushi, Hirokazu; Akazawa, Ryo; Ogata, Hideto; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Uto, Megumi; Mizowaki, Takashi; et al.
Abstract : Background: Patients with osteosarcoma who experience relapse or progression [R/P] have a poor prognosis. Methods: Data from 30 patients who experienced R/P among 59 with a diagnosis of high-grade osteosarcoma, who were younger than 40 years old between 2000 and 2019, were retrospectively analyzed to identify prognostic and therapeutic factors influencing their outcomes. Results: The 5-year overall survival [OS] rates after the last R/P of patients experiencing first [n=30], second [n=14], and third [n=9] R/P were 50.3%, 51.3%, and 46.7%, respectively. Multivariate analysis did not identify any independent risk factors affecting OS. The 5-year PFS rate of the 30 patients after first R/P was 22.4%, and multivariate analysis identified histologic subtype and curative local surgery as independent risk factors influencing PFS. Long [>6 mo] partial response was observed in three patients treated using temozolomide+etoposide, irinotecan+carboplatin, or regorafenib. Conclusions: OS rate in the patients with osteosarcoma experiencing R/P included in this study was markedly higher than that reported previously, mainly due to the surgical total removal of tumors, even after subsequent R/P. The recent establishment of salvage chemotherapy or molecular targeted therapy may also increase survival rates in a subgroup of patients.